Teaching the Historical Jesus in Continuing Education: Of Ghosts and Groundhogs - Meggitt, Justin James (Journal for the study of the historical Jesus, 2025)
This article reflects upon the author’s twenty years of experience in teaching undergraduate-level courses in the study of the historical Jesus outside of a traditional university context as part of the programmes offered by the Institute of Continuing Education of the University of Cambridge. It identifies a number of distinctive pedagogical challenges faced in teaching adult learners, and strategies for addressing them, as well as the wider implications for the field that arise from such teaching activity.